Seasonal Variation in Nitrate Levels in Hand Dug Wells in Makurdi Metropolis - Maxwell, Ocheri; Mile, Iyange; Obeta, M.C. (Pakistan Journal of Nutrition, 2010)
Groundwater quality response to changes in season is documented in several studies. In this study, seasonal variation in nitrate levels in hand dug wells in Makurdi metropolis is examined. A total of 15 water samples were collected from hand dug wells and analyzed for nitrate level for both wet and dry seasons. The analysis was done according to standard method of water examination. The results of analyses show that 80% of the wells have nitrate levels above WHO guide limit for drinking water for the wet season as against 67% for the dry season. This implies that consumers of water from these hand dug wells especially children stands a very high of metheamogolineamia. Generally nitrate level in these hand dug wells were noted to be higher in wet season than in the dry season. Source of nitrate in these wells is attributed to use of chemical fertilizers on farms, improper disposal of animal and human wastes and influence of season. All land use activities capable of polluting water should be properly controlled. Water from these wells may be used for other domestic purposes other than drinking. Boiling of water from these should be encouraged to reduce the risk of contracting illness.